Any neonatal morbidityAdverse perinatal outcomes of unvaccinated pregnant women with respiratory symptoms during the COVID-19 pandemic: Evidence from a Brazilian multicenter study - Da-Costa-Santos, Juliana; dos Reis Junior, Paulo Sergio; Luz, Adriana Gomes; Cecatti, Jose Guilherme; Souza, Renato T.; Tedesco, Ricardo P.; Fernandes, Karayna G.; Martins-Costa, Sérgio H. A.; Peret, Frederico J. A.; Feitosa, Francisco E.; Traina, Evelyn; Cunha Filho, Edson V.; et al. (Wiley, 2025)
Objective: The current study aimed to describe risk factors for adverse perinatal outcomes (APOs) among pregnant women nonvaccinated for COVID-19 who had respiratory symptoms. Methods: A nested case–control study was performed within the REBRACO (in Portuguese, the Brazilian Network of COVID-19 During Pregnancy) initiative. Women were recruited during pregnancy in 15 maternity hospitals in Brazil from February 1, 2020, to February 28, 2021, while seeking medical care for respiratory symptoms, and were followed up until childbirth regardless of confirmation of COVID-19. For this analysis, women were divided into two groups: (1) those with APOs, defined as the occurrence of fetal or neonatal death, preterm delivery, 5-min Apgar score <7, neonatal respiratory distress, neonatal mechanical ventilation, admission to the neonatal intensive care unit, small-for-gestational-age newborn, or any neonatal morbidity; and (2) those without APOs. Results: The total number of women included in this analysis was 481, with 210 having APOs (43.7%). The characteristics independently associated with APOs were a composite outcome of severe acute respiratory syndrome, maternal admission at the intensive care unit, or maternal death (relative risk [RR], 3.30 [95% confidence interval (CI), 1.38–7.89]), living in the North and Northeastern regions of Brazil (RR, 3.09 [95% CI, 1.13–8.41]), and pre-eclampsia (RR, 2.77 [95% CI, 1.19–6.43]). Conclusion: Severe maternal illness was strongly associated with APO regardless of COVID-19 confirmation. It is essential to provide sufficient and timely health care for women who have respiratory symptoms compatible with COVID-19.
Keywords: COVID-19; infectious; perinatal care; pregnancy complications; SARS-CoV-2